Learning - Oriented Assessment in Speaking Class at University Level - Wibowo, J Ari; Syam, Khoirudin Yanuar (English Education:Journal of English Teaching and Research, 2016)
This paper proposes a model of learning-oriented assessment to inform assessment theory and practice in speaking class. It focuses on two interrelated processes: the students’ assessment tasks and student engagement with feedback. The research method involves classroom observations of in English speaking class in university level and semi-structured interviews with the lecturer and some sample of the students’ feedback. Findings highlight assessment tasks promoting thinking and practicing in the speaking activities and direct feedback to promote timely dialogues with students. The coherence of the model is discussed and some areas for further exploration are suggested. Based on the data analysis, the model shows significantly positive outcome. In the student side, it provides clearly path for them to reach the standard goal since they always get negative evidence from the teacher in each time they are out of the track. In the teacher side, it also provides positive effect. As they give negative evidence or correct the student’s mistake, they auomatically need to monitor the student’s development on every stages. It gives a crystal clear sight of student’s improvement. Finally it supports significantly on the assessment reliability of their speaking skill.